Pemberian Terapi Guided Imagery terhadap Pasien dengan Nyeri dan Ansietas Post Operasi Fraktur Collum Humerus - Azizah Nur Khasanah; Syahruramdhani Syahruramdhani (Jurnal Medika Nusantara, 2023)
Background: After the fracture surgery procedure, the patient who initially received anesthesia and a few hours later disappeared, usually the patient will feel pain, apart from pain, anxiety will arise related to changes in daily activity, where these two things are interconnected. An increased response to pain is often caused by a feeling of anxiety or vice versa the response to pain can cause anxiety. Nonpharmacological therapy that can be done by nurses to reduce pain as well as postoperative anxiety is guided imagery therapy. Purpose: This case study aims to determine the effectiveness of guided imagery therapy for pain and anxiety in patients with postoperative humeral collum fractures. Methods: The method used in writing is a case report with guided imagery therapy intervention carried out for 3 days. Results: The results of this case study show that after guided imagery intervention for 3 days there was a decrease in the Numeric Pain Scale from 7 (moderate pain) to 3 (mild pain) and a decrease in the Beck Anxiety Inventory score from 11 (mild anxiety disorder) to 5 (minimal anxiety disorder). Conclusion: Guided imagery is effective in reducing pain and anxiety in postoperative humeral collum fracture patients.